ANALISIS PERBANDINGAN KINERJA REKSA DANA KONVENSIONAL DENGAN REKSA DANA SYARIAH DI INDONESIA - Jepryansyah Putra; syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2014)
This research aims to analyze how the performance between Conventional mutual fund and Sharia mutual fund. Variables that are used in this research are sharpe ratio, treynor ratio, and jensen ratio. By using purposive sampling method, there are21Investment Manager that managed conventional mutual fund and sharia mutual fund. This research used Average Difference to analyze performance between conventional and sharia mutual fund. The result showed sharia mutual funds have a greater return and less risk than conventional mutual funds. Hypothesis test on equity fund performance is different but not significant measured by sharpe ratio and treynor ratio, but while testing by jensen ratio showed significant difference. Hypothesis test on fixed income fund is different but not significant measured by sharpe ratio, jensen ratio, and jensen ratio. Hypothesis test on mixed mutual fund is different but not significant measured by sharpe ratio, treynor ratio, and jensen ratio.Keywords:Mutual fund, Sharpe ratio, Treynor ratio, Jensen Ratio, and Average Difference